2016
DOI: 10.1159/000448621
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of CHK1 Inhibitor LY2603618 in Combination with Gemcitabine in Patients with Solid Tumors

Abstract: Objective: LY2603618, a selective inhibitor of checkpoint kinase 1 (CHK1) and key regulator of the DNA damage checkpoint, may enhance the effects of antimetabolites. This phase I study defined the recommended phase II dose of LY2603618 combined with gemcitabine. Patients and Methods: Patients with advanced/metastatic disease were administered doses of LY2603618 (70-250 mg/m2 or flat-fixed doses of 200 or 230 mg) after gemcitabine (1,000 mg/m2). Safety and pharmacokinetics (PK) were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…As a result of these data, clinical trials with early CHK1 inhibitors focused on the chemopotentiation of cytotoxic drugs. Although phase I trials demonstrated proof of concept that CHK1 inhibitors could be safely combined with chemotherapy (17)(18)(19)(20)(21)(22)(23)(24)(25), phase II studies failed to meet their primary endpoints (26,27). Early CHK1 inhibitors were not successful for a variety of reasons, including pharmacokinetic properties, unacceptable toxicities, and business considerations.…”
Section: Strategies For Clinical Development: Past and Presentmentioning
confidence: 99%
“…As a result of these data, clinical trials with early CHK1 inhibitors focused on the chemopotentiation of cytotoxic drugs. Although phase I trials demonstrated proof of concept that CHK1 inhibitors could be safely combined with chemotherapy (17)(18)(19)(20)(21)(22)(23)(24)(25), phase II studies failed to meet their primary endpoints (26,27). Early CHK1 inhibitors were not successful for a variety of reasons, including pharmacokinetic properties, unacceptable toxicities, and business considerations.…”
Section: Strategies For Clinical Development: Past and Presentmentioning
confidence: 99%
“…As expected, this combined treatment inhibits colony formation (4), increases clonogenic cell death (6) and inhibits tumor growth compared with GEM treatment alone (7)(8)(9)(10). Phase I clinical trials have been initiated, and the recommended phase II dose has been shown (11)(12)(13)(14)(15). However, concerns about unpredicted effects of Chk1 inhibitors on normal cells have been raised (12,16).…”
Section: Introductionmentioning
confidence: 89%
“…Most of the CHK1i clinical trials have been in combination with gemcitabine, the standard-of-care drug in many cancer types, which is usually used in maximum tolerated dose (MTD) when combined with CHK1i and potentially resulted in enhanced normal tissue toxicity as reported in previous clinical trials (Calvo et al, 2016, Infante et al, 2016, Sausville et al, 2014, Doi et al, 2015. Utilising low-dose HU would be more clinically feasible since HU is not standard-of-care but approved drug in many cancer types and would probably result in less toxicity to normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…CHK1 inhibitors have been investigated in preclinical studies and clinical trials in combination with chemotherapeutic agents. Despite the initial hope it offered, CHK1 inhibitor in combination with chemotherapeutic drugs have shown varying efficacies in patients (Seto et al, 2013, Sausville et al, 2014, Calvo et al, 2016, Doi et al, 2015. More specific CHK1 inhibitors were developed along the way and their efficacy to enhance chemotherapy were also being evaluated and reported to be more successful than the previous attempts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation